Outgrowing God : a beginner's guide - Dawkins, Richard, 1941- (Bantam Press, 2019)
Should we believe in God? In this new book, written for a new generation, the brilliant science writer and author of The God Delusion, explains why we shouldn't. Should we believe in God? Do we need God in order to explain the existence of the universe? Do we need God in order to be good? In twelve chapters that address some of the most profound questions human beings confront, Dawkins marshals science, philosophy and comparative religion to interrogate the hypocrisies of all the religious systems and explain to readers of all ages how life emerged without a Creator, how evolution works and how our world came into being. For anyone hoping to grapple with the meaning of life and what to believe, Outgrowing God is a challenging, thrilling and revelatory read.